The Influence of Employee Development Initiatives in the Retention of Academics at Kyambogo University, Uganda - Sebastian Bigabwenkya; Elizabeth Binta (Ugandan Journal of Management and Public Policy Studies, 2024)
The study analysed the influence of employee development (ED) initiatives on the retention of academics at Kyambogo University (KYU) in Uganda. The issue of concern was that whereas KYU was investing up to 18% of her annual budget into staff hiring and development activities, the contribution of these ED activities or initiatives towards the retention of academics was not known. Hence, the study’s overall objective was to assess the influence of ED initiatives on the retention of academics at KYU. The study,, borrowing ideas from the job embeddedness theory, explains how staff retention at KYU is partly a question of being embedded in the university employment system and partly due to other factors. The study adopted an explanatory survey design that employed quantitative data collection and analysis approaches. Stratified sampling techniques were used to select a sample of 159 from a study population of 311 academics. A self-administered questionnaire was used to collect data. The study registered a response rate of 68.2% (107 out of 157). The data were analysed using SPSS Version 25 and presented as descriptive and inferential statistics. The key findings from the study revealed that ED had a significant positive correlation with academic retention (r = 0.489**, n= 107, p = 0.000). It was also established that ED is a significant predictor of retention of academics at KYU (F = 33.010, p< 0.01). Up to 23.2 per cent of the variance in the retention of academics at the university could be attributed to ED initiatives. It was concluded that if ED initiatives were effectively implemented, there would be a likelihood of improving retention levels of academics. The study recommends that the administration of KYU maintains the existing ED initiatives and strengthens them further to attain a high level of retention of academics. The study further recommends maintaining and improving the existing practices of ED, such as mentoring, coaching, lectures, workshops and conferences.